تأثير استخدام تمرينات البليومترك في الماء على تحسين مستوى الإنجاز في سباق عدو 100م - بجبوج, فؤاد; الطواشي, رهام (Latakia University Journal -Medical Sciences Series, 2018)
هدفت هذه الدراسة إلى التعرف على تأثير استخدام تمرينات البليومترك في الماء على تحسين مستوى الإنجاز في سباق عدو 100م لدى لاعبي منتخب جامعة حماه ,ولهذا وضعت تمرينات البليومترك المائية في برنامج تدريبي تم ترشيحه على عدة خبراء مختصين , وتكونت عينة البحث من (12) لاعباً من لاعبي منتخب جامعة حماه ,وتم استخدام المنهج التجريبي بأسلوب المجموعتين المتكافئتين (التجريبية-الضابطة) , وقد خضعت المجموعة التجريبية للبرنامج التدريبي المقترح , بينما خضعت المجموعة الضابطة إلى تمريناتهم الاعتيادية , ولقد طبق اختبار عدو 100 م غلى المجموعتين الضابطة والتجريبية قبل تنفيذ البرنامج وبعده , وتم مقارنة النتائج بينهما,وتوصلت الدراسة إلى أن تمرينات البليومترك المائية أثرت تأثيراً إيجابياً على تحسين مستوى الإنجاز في عدو 100م لدى المجموعة التجريبية التي طبقت البرنامج التدريبي . The aim of this study was to identify the effect of the use of water plyometric exercises on improving the level of achievement in the 100 meter race in the players of the University of Hama. Therefore, These exercises were developed in a training program that was nominated by several specialized experts. The sample consisted of (12) players from the University of Hama. The experimental method was used in the two groups (experimental - control) Experimental for the experimental program And the control group underwent their normal exercises. A 100 meter test was applied to the control and experimental groups before and after the program was implemented. The results were compared. The study concluded that the plyometric water exercises had a positive effect on improving the achievement level in the 100 meters race in the group which applied the training program.